NUCLEAR POWER AND ITS ROLE IN LIMITING CO2 EMISSIONS - Suparman Suparman (Pusat Kajian Sistem Energi Nuklir, Badan Tenaga Nuklir Nasional, 2012)
ABSTRACTNUCLEAR POWER AND ITS ROLE IN LIMITING CO2 EMISSIONS. The objective of this study is to analyze the proper role of nuclear power in the long term energy planning by comparing different type of scenarios in terms of CO2 emission reduction, based on the Business-as-Usual (BAU) scenario. For this purpose, a MESSAGE (Model of Energy Supply Systems and their General Environmental impacts) was used to develop energy planning as well as CO2 emission projection. A sensitivity analysis for CO2 reduction rates of 2%, 3%, 4% and 5% have been done. From this sensitivity analysis, it can be concluded that nuclear will be a part of optimum solution under CO2 limitation of at least 3% from BAU condition. The more the environmental standards are tightened and enforced the more and the earlier nuclear power becomes part of the optimum generation mix.Keywords: nuclear energy, CO2 emission ABSTRAKENERGI NUKLIR DAN PERANNYA DALAM PEMBATASAN EMISI CO2. Tujuan dari studi ini adalah untuk melakukan analisis peran dari energi nuklir dalam perencanaan jangka panjang dengan cara membandingkan beberapa skenario yang berbeda dalam hal pengurangan emisi CO2, didasarkan pada skenario Business-as-Usual (BAU.) Untuk tujuan ini, model MESSAGE (Model of Energy Supply Systems and their General Environmental impacts) digunakan guna menyusun perencanaan energi termasuk proyeksi emisi CO2. Analisis sensitivitas untuk tingkat pengurangan CO2 dibuat dengan besaran 2%, 3%, 4% and 5%. Dari analisis sensitivitas dapat disimpulkan bahwa nuklir akan menjadi bagian dari solusi optimal pada kondisi pembatasan CO2 minimal 3% dari skenario BAU. Semakin ketat dan pemaksaan standar lingkiungan akan semakin awal energi nuklir menjadi bagian dari bauran pembangkitan yang optimal.Kata kunci: energi nuklir, emisi CO2